2008
DOI: 10.1007/s10040-007-0267-9
|View full text |Cite
|
Sign up to set email alerts
|

Developing conceptual hydrogeological model for Potsdam sandstones in southwestern Quebec, Canada

Abstract: Follow this and additional works at: http://digitalcommons.unl.edu/usgsstaffpub Part of the Earth Sciences CommonsThis Article is brought to you for free and open access by the US Geological Survey at DigitalCommons@University of Nebraska -Lincoln. It has been accepted for inclusion in USGS Staff --Published Research by an authorized administrator of DigitalCommons@University of Nebraska -Lincoln. Nastev, M.; Morin, Roger H.; Godin, R.; and Rouleau, A., "Developing conceptual hydrogeological model for Potsdam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 7 publications
0
26
0
3
Order By: Relevance
“…Based on the few available results from multi-well pumping tests conducted under unconfined conditions, the average specific yield, essentially equivalent to the effective porosity, was evaluated at 1% for all rock units (Nastev et al, 2006;Nastev et al, 2008). The storage in the regional aquifers can then be obtained as a product of the saturated aquifer volume and the effective porosity.…”
Section: Groundwater Balancementioning
confidence: 99%
“…Based on the few available results from multi-well pumping tests conducted under unconfined conditions, the average specific yield, essentially equivalent to the effective porosity, was evaluated at 1% for all rock units (Nastev et al, 2006;Nastev et al, 2008). The storage in the regional aquifers can then be obtained as a product of the saturated aquifer volume and the effective porosity.…”
Section: Groundwater Balancementioning
confidence: 99%
“…Dans le sud du Québec, des études de caractérisation hydrogéologiques régionales ont fourni au cours des dernières années des informations très utiles pour comprendre le fonctionnement de certains aquifères (CLOUTIER et al, 2006;CROTEAU, 2006;FAGNAN et al, 1999;NASTEV et al, 2008;NASTEV et al, 2005). Le programme de cartographie des eaux souterraines de Ressources naturelles Canada a également donné lieu à des études similaires sur d'importants aquifères ailleurs au Canada (RIVERA, 2004).…”
Section: Introductionunclassified
“…Geophysical logs of selected wells indicate that each lithology supports its own flow system and is characterized by a distinct vertical anisotropy (Morin et al, 2007;Nastev et al, 2008). However, drawdown data from large-scale pumping tests yield single permeability type curves typical for porous media, which are analyzed conventionally using the Theis method (Freeze and Cherry, 1979).…”
Section: Regional Groundwater Flowmentioning
confidence: 99%
“…Such high anisotropy values are consistent with observations from previous hydrogeological studies, which identified that the groundwater flow on Covey Hill is sustained mainly through sub-horizontal, laterally extensive fractures. The respective horizontal hydraulic connectivity is very good, but in a vertical direction it is very poor, such that each of the waterbearing bedding planes can be considered as a separate planar two-dimensional aquifer unit (Nastev et al, 2008). Figure 5 presents the 153 measured heads against the simulated heads.…”
Section: Calibrationmentioning
confidence: 99%